ER stress and calcium-dependent arrhythmias - Hamilton, Shanna; Terentyev, Dmitry (Frontiers in Physiology, 2022)
The sarcoplasmic reticulum (SR) plays the key role in cardiac function as the major source of Ca2+ that activates cardiomyocyte contractile machinery. Disturbances in finely-tuned SR Ca2+ release by SR Ca2+ channel ryanodine receptor (RyR2) and SR Ca2+ reuptake by SR Ca2+-ATPase (SERCa2a) not only impair contraction, but also contribute to cardiac arrhythmia trigger and reentry. Besides being the main Ca2+ storage organelle, SR in cardiomyocytes performs all the functions of endoplasmic reticulum (ER) in other cell types including protein synthesis, folding and degradation. In recent years ER stress has become recognized as an important contributing factor in many cardiac pathologies, including deadly ventricular arrhythmias. This brief review will therefore focus on ER stress mechanisms in the heart and how these changes can lead to pro-arrhythmic defects in SR Ca2+ handling machinery.